Asyryjska diaspora Izraelitów w świetle Księgi Ezechiela – Wojciechowi Pikorowi w odpowiedzi - Chrostowski, Waldemar (The Biblical Annals, 2015)
The article opposes the main thesis of W. Pikor who argues against the existence and crucial importance of the Israelite Diaspora in Assyria and against viewing it as an important factor seriously influencing the message of the prophet Ezekiel and his book. In the first part of the article its author scrutinizes the Ezechielian texts questioned by W. Pikor as direct or indirect arguments for the existence of the Assyrian Diaspora. In the second part the possible existence of the Assyrian Diaspora is examined, taking that the Book of Ezekiel bears witness to the Babylonian Diaspora of the Judean exiles, who in the first decades of the sixth century B.C. met the descendants of the Israelites exiled to Assyria at the end of the eight century B.C. The message of Ezekiel, as it may be known from his book, answers the questions and challenges which resulted from an unprecedented meeting of two different, but at the same time cognate groups, namely the Israelites and Judeans, preparing thus the ground for the idea of the renewed “new Israel”.